Microwave-assisted extraction of phenolic compounds from Carica papaya leaves: An optimization study and LC-QTOF-MS analysis - Alara, Oluwaseun Ruth; Abdurahman, N.H.; Ali, H.A.; Zain, N.M. (Elsevier B.V., 2021)
Carica papaya is a well-known plant with diverse importance to human beings. The efficacy of microwave-assisted extraction (MAE) in the recovery of phenolic compounds from C. papaya leaf was investigated in this study. The MAE process variables were optimized using response surface method; at the optimized conditions, the embedded phenolic compounds in the extract were identified through LC-QTOF-MS analysis. The results showed that the best MAE conditions were: time of irradiation at 3 min; microwave power of 420 W; feed-to-solvent ratio of 1:12 g/mL; and solvent concentration of 56% ethanol/water to achieve 102.59 mg GAE/g d.w. of total phenolic content (TPC). At these conditions, an aggregate of 72 phenolic compounds was tentatively identified. These results infer that MAE as a technique can recover phenolic compounds from C. papaya leaf. Hence, the identified compounds can further be quantified with their respective pharmacological properties in future studies.